2021
DOI: 10.1097/sla.0000000000005161
|View full text |Cite
|
Sign up to set email alerts
|

Extended Versus Standard Complete Mesocolon Excision in Sigmoid Colon Cancer

Abstract: The aim of this study was to evaluate whether extended complete mesocolic excision (e-CME) for sigmoid colon cancer improves oncological outcomes without compromising morbidity or functional results. Background: In surgery for cancer of the sigmoid colon and upper rectum, s-CME removes the lymphofatty tissue surrounding the inferior mesenteric artery (IMA), but not the lymphofatty tissue surrounding the portion of the inferior mesenteric vein that does not run parallel to the IMA. Evidence about the safety and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
9
0
1
Order By: Relevance
“…Actually in the study by Mari GM et al, both LT and HT led to impaired sexual and urinary performance, while sexual and urinary performance after LT improved more significantly than that after HT [ 37 ]. However, in two other studies, HT was not significantly different from LT in terms of male genitourinary function of patients with sigmoid colon cancer [ 39 , 40 ]. Interestingly, LT was not significantly different from HT in terms of male genitourinary function, while LT was superior to HT in terms of sexual and urinary performance.…”
Section: Discussionmentioning
confidence: 90%
“…Actually in the study by Mari GM et al, both LT and HT led to impaired sexual and urinary performance, while sexual and urinary performance after LT improved more significantly than that after HT [ 37 ]. However, in two other studies, HT was not significantly different from LT in terms of male genitourinary function of patients with sigmoid colon cancer [ 39 , 40 ]. Interestingly, LT was not significantly different from HT in terms of male genitourinary function, while LT was superior to HT in terms of sexual and urinary performance.…”
Section: Discussionmentioning
confidence: 90%
“…The different effects of laparoscopic surgery vs open surgery in CRC were explored, 22 and an association between CRC and specified surgery in terms of prognosis was found. 23 In a randomized-controlled trial comparing extended complete mesocolic excision (CME) vs standard CME in SCC, Planellas P et al 24 found the total number of lymph nodes, DFS, and OS had no significant difference in the comparison of the two surgical procedures. Our results were similar with their outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors have attempted to also assign an oncological role to this procedure, asserting that it can substantially increase the number of resected lymph nodes along the root of the IMV, potentially influencing both the survival and the local recurrence rate [ 47 , 48 ]. However, the published data have shown contrasting results, likely due to the heterogeneity in the patient population, leaving the oncological significance of the IMV ligation uncertain [ 49 , 50 ]. Only one recent multicenter randomized controlled trial explored the effects of an extended lymphadenectomy in sigmoid colon cancer [ 50 ].…”
Section: The Surgeon- and Patient-centric Approach: The Different Lev...mentioning
confidence: 99%
“…However, the published data have shown contrasting results, likely due to the heterogeneity in the patient population, leaving the oncological significance of the IMV ligation uncertain [ 49 , 50 ]. Only one recent multicenter randomized controlled trial explored the effects of an extended lymphadenectomy in sigmoid colon cancer [ 50 ]. Their findings indicated that including the lymphatic area around the IMV did not result in a higher total node count or a greater detection of positive nodes.…”
Section: The Surgeon- and Patient-centric Approach: The Different Lev...mentioning
confidence: 99%